A review of wearable antenna - Rais, N. H M; Soh, Ping Jack; Fareq, Malek; Sahadah, Ahmad; Nur Baya, Mohd Hashim; Hall, Peter S. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/